Customers satisfaction towards the products given by Petronas LPG in Kuantan areas / Syazreen Abdul Ghani (Faculty of Business and Management, 2007)
This research was carried out to obtain information about customer's satisfaction towards the products given by Petronas LPG in Kuantan areas from the customers view point. This study was based on probability sampling design which is used simple random sampling to gather all the information regarding the customer's satisfaction towards the products given by Petronas LPG in Kuantan areas. The data was collected through faceto- face interviews by using personally administered questionnaire. The overall findings frequency counts for 74 respondent's shows that majorities of the respondents are Malaysian and most of them are Malay. For gender, most of the respondents are female and married. The age of the respondents mostly from 26 - 35 years old and above 45 years old. Majority of the respondents work in government sector and earn monthly salary between RM 2000 - RM 3000. There is positive relationship between selected demographics with customer satisfaction, where majority are agreeing and satisfied with the statement that rate their satisfaction towards Petronas LPG in Kuantan areas. Recognizing the problems and products given by Petronas LPG, can therefore give a general guidance to improve the products and customer service given as well as gaining customers satisfaction while enhance the overall products and services.